Identifikasi lanskap Karang Bengang di Desa Buahan, Kecamatan Tabanan, Kabupaten Tabanan - Wijaya, I Gede Komang Adi; Utami, Ni Wayan Febriana; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020, 2020)
Landscape identification of karang bengang at Buahan Village, Tabanan Subdistrict, Tabanan Regency. This research is motivated by the absence of the spatial pattern of landscape character of karang bengang at Buahan Village. Karang bengang is an open space that is located between the villages as a nonresidential area. The existence of karang bengang increasingly rare in Bali, due to land use change. This study aims to identify and map the spatial patterns and characters of karang bengang at Buahan Village, Tabanan sub-district, Tabanan Regency. The method used in this research was survey method and data  were collected by conducting observation, interviews, and literature study. For data analysis, it used qualitative data analysis methods and the results was presented in the form of illustration of spatial pattern of Tabanan Subdistrict, illustration of the spatial pattern of Desa Buahan, and map of the karang bengang area at Buahan Village. Based on the analysis, it was found that the landscape character of karang bengang at Buahan Village was influenced by biophysical (climate, accessibility, softscape, and hardscape, spatial patterns, land cover) and social aspects (demographic, socio-cultural, and economic), as well as traditional Balinese space patterns of Tri Hita Karana (the concept of reciprocity of humans with nature implements natural use areas such as pancoran, rice fields, fields, humans and humans implementing human interaction areas such as farmer huts, humans and God implement sacred areas such as Pelinggih Catu to achieve harmony) and Tri Mandala (the concept of division of three levels of space). Furthermore, the role of the community element is needed in strengthening the village-owned regulation and village construction in order to preserve the karang bengang at Buahan Village.